Reintroduksi Filosofi Wayang melalui Seni Rupa Kontemporer - Oktoviandy, Rizky (Jurnal SeniRupa Warna, 2026)
This paper discusses the discourse on the reintroduction of the philosophical values of wayang through contemporary Indonesian visual art. Wayang is understood not merely as a form of entertainment, but as a symbolic system that embodies moral guidance through semiotic and psychoanalytic approaches. Every element of wayang, including its characters, the gunungan, and the structure of the performance itself, represents moral values, social principles, and psychological reflections of human life. However, with the progression of modern times, the relevance of wayang has gradually declined, particularly among younger generations, who tend to understand it superficially without exploring its deeper philosophical meanings. Within the practice of modern visual art, several artists, such as Otto Djaya, T. Sutanto, and Nyoman Gunarsa, have creatively integrated wayang elements through contextual and symbolic visual approaches. Nevertheless, within the realm of contemporary visual art, wayang is often reduced to a decorative element without substantial conceptual exploration. This study identifies a major challenge in the limited literacy of artists, curators, and galleries regarding the essential values of wayang, which consequently weakens the philosophical representation embedded in artistic works. Therefore, greater collaboration among various actors within the visual arts ecosystem, accompanied by more comprehensive conceptual approaches, is necessary to position wayang as a primary source of inspiration rather than merely a visual ornament. In this regard, contemporary visual art has the potential to serve as a strategic medium for bridging tradition and modernity while reintroducing wayang to a broader audience, particularly younger generations.